SISTEM INFORMASI TIME SHEET GOPOOL(SI-TEGOL) BERBASIS WEBSITE PADA PT SCHLUMBERGER MENGGUNAKAN METODE PROTOTIPE - Basri, Hasan; Fauzi, Mohamad; Supriadi, Deddy; Azis, Mohammad Syamsul (INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS : Journal of Information System, 2024)
The design of a website-based gopool time sheet information system at PT Schlumberger aims to increase efficiency and accuracy in managing gopool time sheets. This research uses field research methods through observation, interviews and literature study. PT Schlumberger is currently still implementing a manual recording system in managing gopool time sheets. The research results show that designing the Gopool time sheet system provides significant benefits. First, this system makes it easier to organize and manage Gopool time sheet data. Inputting employee data and time sheets becomes more efficient and accurate. Second, the design of this system allows the creation of gopool time sheet reports quickly and accurately. It is important to design the Gopool time sheet system by involving all related parties and carrying out adequate training for staff. In this way, PT Schlumberger can utilize an efficient and integrated Gopool time sheet system, increasing the effectiveness of Gopool time sheet management.